Dichotic listening performance in children with dyslexia. (10th December 2014) - Kumar, Prawin; Gupta, Rohit Kumar
The present study aimed to compare the dichotic listening task in children with dyslexia and typically developing children using dichotic consonant vowel test. Twenty children in the age range of 10 to 12 years were taken in the present study. Ten children with dyslexia were served as experimental group whereas another ten age–matched typically developing children were considered as control group. The results revealed that dichotic consonant vowel scores were significantly reduced in children with dyslexia compared to typically developing children for single correct score of right and left ear as well as double correct scores at 0.05 levels of significance. Further, it was also observed that children with dyslexia showed left ear advantage instead of right ear advantage as seen in typically developing children. Hence, it is concluded that children with dyslexia performed poorly in dichotic listening task and direction of ear advantage was also different compared to typically developing children.